Evaluation of the effects of Aegle marmelos and Punica granatum in an experimental model of gastrointestinal barrier dysfunction - M. Malhi, Harshveer Singh; Kamat, Sandhya K.; Deogharkar, Akash R.; Rege, Nirmala N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The study was conducted to evaluate the effects of Aegle marmelos and Punica granatum in an experimental model of gastrointestinal barrier dysfunction induced by common bile duct ligation. Methods: Institutional animal ethics committee approval was obtained. Forty two Wistar rats (either sex, 150-250 gms) divided into seven groups (n=six/group), were subjected to sham operation (group 1) or bile duct ligation (groups 2-7) and treated with distilled water (groups 1 and 2); 0.75mg/kg glutamine (group 3); 0.27 g/kg and 0.54 g/kg of A. marmelos (groups 4 and 5); 3.6 g/kg and 7.2 g/kg P. granatum (groups 6 and 7) orally once daily for 10 days. On Day 11, animals were sacrificed and samples of the jejunum, ileum and mesenteric lymph nodes were obtained to study jejunal and ileal villous morphology, villous heights, jejunal mucosal sucrase enzyme activity and bacterial translocation to mesenteric lymph nodes. Results: Glutamine prevented blunting of the intestinal villi, bacterial translocation and a fall in the sucrase enzyme activity. Both the plant drugs prevented blunting of the villi (except low dose A. marmelos for ileal villi) and a fall in the villous heights (except low dose P. granatum for jejunal villi), decreased the bacterial translocation (except low dose A. marmelos), and prevented a fall in the sucrase enzyme activity when compared to the disease control. The high doses of both A. marmelos and P. granatum were comparable to glutamine for all the variables tested. Conclusions: Both A. marmelos and P. granatum maintained the gastrointestinal barrier function in this model.